2023
DOI: 10.1093/bib/bbad087
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking genome assembly methods on metagenomic sequencing data

Abstract: Metagenome assembly is an efficient approach to reconstruct microbial genomes from metagenomic sequencing data. Although short-read sequencing has been widely used for metagenome assembly, linked- and long-read sequencing have shown their advancements in assembly by providing long-range DNA connectedness. Many metagenome assembly tools were developed to simplify the assembly graphs and resolve the repeats in microbial genomes. However, there remains no comprehensive evaluation of metagenomic sequencing technol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 67 publications
2
26
0
Order By: Relevance
“…We downloaded the metagenomic sequencing datasets from CAMI I with low, medium (two datasets), and high complexity and from a human stool sample ( S 1 ) [25]. The contigs of these datasets were assembled by metaSPAdes with default parameters.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We downloaded the metagenomic sequencing datasets from CAMI I with low, medium (two datasets), and high complexity and from a human stool sample ( S 1 ) [25]. The contigs of these datasets were assembled by metaSPAdes with default parameters.…”
Section: Methodsmentioning
confidence: 99%
“…We observed that Deepurify outperformed two state-of-the-art tools MAGpurify and MDMcleaner in simulated, CAMI I challenge (high, medium1, medium2, and low) [24] and human gut metagenomic sequencing data [25, 26]. For simulated data, chimeric MAGs were created by mixing the sequences from two microbial genomes at various taxonomic ranks, with contamination rates from 5% to 20%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One main strategy is to assemble short reads and then bridge gaps with long reads, leading to assemblies that are accurate but less contiguous 1,5,8,11,14,18,19 .…”
mentioning
confidence: 99%